Quality of life in adult patients with congenital heart disease: Results of a double-center study - Khajali, Zahra; Sayyadi, Amin; Ansari, Zahra; Aliramezany, Maryam (Frontiers in Psychiatry, 2023)
Introduction Prevalence of congenital heart disease (CHD) has increased in recent years, and patients with CHD have to deal with sequelae of the multiple medical and surgical treatments that can affect different aspects of their life which could be reflected in their quality of life (QoL). In Iran, to the best of our knowledge, QoL of adult patients with CHD has not been investigated, so this study aimed to investigate the QoL of adult patients with CHD referred to two Iranian outpatient settings. Methods In 2022, a double center, cross-sectional study was performed on adult patients with CHD receiving out-patient care at Besat Clinic in Kerman, Iran, and Clinic of Shahid Rajaee Hospital in Tehran, Iran. Inclusion criteria were documented diagnosis of CHD based on guidelines, ejection fraction of above 45% and age of 18–55 years. We recruited a sample of 120 individuals using a simple random sampling method. At the day of referring to the adult congenital heart diseases clinic, after ensuring their written consent to participate in the study, we asked patients to fill in two questionnaires of demographic questionnaire and Persian version of the Ferrans and Powers Quality of Life Index. Data were analyzed using descriptive statistics and chi square via SPSS-22. Results A total of 101 patients with a mean age of 31.05 years participated in the study. Demographic and socio-economic factors had no significant relationship with the patients’ QoL. But factors related to the disease were significantly different among QoL groups (P-value > 0.05). Discussion Adults with CHD had a low QoL, which is not related to their demographic and socio-economic factors. That is, the existence of the disease alone and its accompanying complications can affect the QoL of these people. Hence, the mental health of adult patients with CHD should be monitored during their routine cardiac care.